الخصومة النقدية بين القدماء والمحدثين - توتو, يوسف محمد (Gezira Journal of Educational Sciences and Humanities; Vol 17 No 2 (2020), 2021)
مستخلص الدراسة       هدفت الدراسة إلى التعرُّف على الخُصومة النقدية بين القدماء والمحدثين من حيث أطرافها ومظاهرها وقضاياها ، اتبعت المنهج الوصفي التحليلي ، توصلت إلى عدة نتائج منها: إنّ الخصومة النقدية بين القدماء والمحدثين أولى المعارك النقدية في تاريخ النقد الأدبي ، أثارت قضايا نقدية تتصل بالنقد الأدبي منهجاً ومضموناً ، تعد الخصومة النقدية مظهراً من مظاهر تطور النقد الأدبي نظراً لطبيعة القضايا التي أثارتها والمؤلفات النقدية التي حوتها ، توصي الدراسة بتناول أثر الخصومة النقدية بين القدماء والمحدثين على تطور النقد الأدبي القديم. Abstract    The study aimed to identify the critical antagonism between the ancients and the modernisms in terms of its parties, manifestations and issues. It followed the descriptive and analytical approach, and reached several conclusions, including: The critical antagonism between the ancients and modernisms is the first critical battle in the history of literary criticism, and it raised critical issues related to literary criticism, method and content, Critical rivalry is a manifestation of the development of literary criticism due to the nature of the issues it raised and the critical literature it contained. The study recommends addressing the impact of the critical rivalry between the ancients and the modernists on the progressing of ancient literary criticism.